2020
DOI: 10.1038/s41467-020-17824-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential chloride homeostasis in the spinal dorsal horn locally shapes synaptic metaplasticity and modality-specific sensitization

Abstract: GABA A /glycine-mediated neuronal inhibition critically depends on intracellular chloride (Cl −) concentration which is mainly regulated by the K +-Cl − co-transporter 2 (KCC2) in the adult central nervous system (CNS). KCC2 heterogeneity thus affects information processing across CNS areas. Here, we uncover a gradient in Cl − extrusion capacity across the superficial dorsal horn (SDH) of the spinal cord (laminae I-II: LI-LII), which remains concealed under low Cl − load. Under high Cl − load or heightened syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 103 publications
(196 reference statements)
1
65
1
1
Order By: Relevance
“…It is well established that BDNF release in the SDH is involved in neuropathic pain 10 , 16 , 17 . However, to our knowledge our findings are the first to show chronic BDNF treatment unmasks [Ca 2+ ] i fluctuations in a subpopulation of SDH neurons while depressing activity in others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that BDNF release in the SDH is involved in neuropathic pain 10 , 16 , 17 . However, to our knowledge our findings are the first to show chronic BDNF treatment unmasks [Ca 2+ ] i fluctuations in a subpopulation of SDH neurons while depressing activity in others.…”
Section: Resultsmentioning
confidence: 99%
“…This ‘central sensitization’ is thought to be responsible for the allodynia, hyperalgesia, spontaneous pain and causalgia that characterize neuropathic pain 3 , 15 . Spinal actions of BDNF involve alteration in Cl - gradients such that the normally inhibitory actions of GABA become excitatory 16 , 17 . There is also increased excitatory synaptic drive to putative excitatory neurons 9 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that even a robust downregulation of KCC2 activity does not abolish inhibitory postsynaptic potentials (IPSPs) if cellular Cl − regulation is challenged by a Cl − load [ 58 ] and, besides, that this may take place at a low rate. Finally, Ferrini et al recently uncovered a gradient in Cl − extrusion capacity via the superficial dorsal horn of the spinal cord (laminae I-II), which remains concealed under a low Cl − load [ 11 ]. Under a high Cl − load or a heightened synaptic drive, low Cl − extrusion occurred via the expression of KCC2.…”
Section: Cccs and Gaba A R Activitymentioning
confidence: 99%
“…Indeed, in mature neurons, a low [Cl − ] i renders the reversal potential for GABA (E GABA ) more hyperpolarized than the membrane potential (E M ) [ 8 ]. The interaction of GABA with synaptic or extrasynaptic GABA A Rs leads to Cl − influx into the neurons and the hyperpolarization of E M [ 9 , 10 , 11 ]. Under certain circumstances (for example, massive activation), GABA A ergic signaling can be switched from fast hyperpolarization to long-term depolarization of the E M [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This ‘central sensitization’ is thought to be responsible for the allodynia, hyperalgesia, spontaneous pain and causalgia that characterize neuropathic pain (3,15). Spinal actions of BDNF involve alteration in Cl - gradients such that the normally inhibitory actions of GABA become excitatory (16,17). There is also increased excitatory synaptic drive to putative excitatory neurons (9,18).…”
Section: Introductionmentioning
confidence: 99%